2017
DOI: 10.1002/etc.3978
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of earthworm sublethal toxic responses to atrazine exposure using 1H nuclear magnetic resonance (NMR)‐based metabolomics

Abstract: Atrazine toxicity to earthworms is still not fully understood, particularly at sublethal concentrations. Because of the ubiquity of atrazine in the environment, it is imperative to understand the impacts of atrazine presence to soil-dwelling organisms. To examine this in detail, we used H nuclear magnetic resonance (NMR)-based metabolomics to elucidate earthworm (Eisenia fetida) responses after 48 h of atrazine exposure in contact tests. Earthworms were exposed to 4 sublethal concentrations of 362.4, 181.2, 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…glucose storage – gluconeogenesis). Similar results were reported for other invertebrates such as the fruit fly Drosophila melanogaster , 50 while in Enchytraeus albidus (enchytraeid) 51 and Eisenia fetida (earthworm), 52 gluconeogenesis was enhanced in response to atrazine exposure, although at a shorter exposure period – 2 days. The differences between the two enchytraeid species ( E. crypticus and E. albidus ) could be related to the different sensitivities reported towards ATZ exposure.…”
Section: Discussionsupporting
confidence: 84%
“…glucose storage – gluconeogenesis). Similar results were reported for other invertebrates such as the fruit fly Drosophila melanogaster , 50 while in Enchytraeus albidus (enchytraeid) 51 and Eisenia fetida (earthworm), 52 gluconeogenesis was enhanced in response to atrazine exposure, although at a shorter exposure period – 2 days. The differences between the two enchytraeid species ( E. crypticus and E. albidus ) could be related to the different sensitivities reported towards ATZ exposure.…”
Section: Discussionsupporting
confidence: 84%
“…However, shifts in the lipid metabolome observed at our highest naphthenic acid exposure level indicate that a biochemical response may be initiated at levels approximating our highest treatment level (100 μg L −1 ) suggesting a potential threshold for naphthenic acid effects. Such threshold responses have been observed in other studies assessing non-lethal levels of contaminants using metabolomics (e.g., (Lankadurai et al, 2011a;Lankadurai et al, 2011b;Dani et al, 2018). However, because we limited our study to concentrations currently observed in aquatic environments and the evidence for a potential threshold occurs at the highest concentration tested in our study we cannot confirm this form of response from our results.…”
Section: Metabolitementioning
confidence: 45%